(untitled) (Fiep Bulletin - online, 2012)
Cardiovascular diseases are major public health problem not only in Brazil but all over the world, affecting than sedentary individuals, athletes from different sports, especially those who use anabolic androgenic steroid. The objective of this study was to determine the prevalence of risk factors for coronary heart disease in athletes bodybuilders from city of Natal - RN. Additionally, we analyzed the risk of developing coronary disease population, and the association between age, training time and percentage of fat with risk for this disease. This study was observational and not experimental cross section, in which 26 subjects men bodybuilders were enrolled who were analyzed for the following: family history, cigarette smoking, hypertension, dyslipidemia, altered glucose levels, obesity and sedentary lifestyle. These variables were observed through a descriptive univariate analysis, determining thus the prevalence of each risk factor, as well as the risk classification, and the association between variables were analyzed using Fisher’s exact statistical test using the SPSS software for Windows® version 17.0. The most prevalent risk factors were: dyslipidemia (80,8%), hypertension (42,3%) and altered glucose levels (15,4%). Within the levels of risk classification, met: low risk (50%), moderate risk (38,5%), high risk (11,5%). Reported a significant association between age (over 29) and moderate/high risk (p=0,005; RP=3,95). Given the high prevalence of dyslipidemia and half the athletes are the moderate/high risk, we suggest the adoption of preventive measures in order to protect against the consequences of coronary artery disease in subjects over 29 years of age.